2019
DOI: 10.12688/f1000research.17242.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding and managing adenomyosis

Abstract: Adenomyosis is a benign uterine disorder in which endometrial glands and stroma are pathologically demonstrated in the uterine myometrium and it is considered a specific entity in the PALM-COEIN FIGO (polyp; adenomyosis; leiomyoma; malignancy and hyperplasia; coagulopathy; ovulatory dysfunction; endometrial; iatrogenic; and not yet classified – International Federation of Gynecology and Obstetrics) classification of causes of abnormal uterine bleeding (AUB). Although it has always been considered the classic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
174
0
25

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(199 citation statements)
references
References 83 publications
0
174
0
25
Order By: Relevance
“…It is characterized by the presence of endometrial stroma and glands within the myometrium and its main clinical features include chronic pelvic pain, abnormal uterine bleeding, menorrhagia, dysmenorrhea, dyspareunia and infertility . In recent years, due to the advancement of imaging techniques such as transvaginal ultrasound scan (TVUS) and magnetic resonance imaging (MRI), substantial evidences suggest that adenomyosis may develop more often among younger women . To date, no novel compound is reported to develop for adenomyosis and clinical studies on the well‐conducted pharmacologic treatment are seldom reported .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by the presence of endometrial stroma and glands within the myometrium and its main clinical features include chronic pelvic pain, abnormal uterine bleeding, menorrhagia, dysmenorrhea, dyspareunia and infertility . In recent years, due to the advancement of imaging techniques such as transvaginal ultrasound scan (TVUS) and magnetic resonance imaging (MRI), substantial evidences suggest that adenomyosis may develop more often among younger women . To date, no novel compound is reported to develop for adenomyosis and clinical studies on the well‐conducted pharmacologic treatment are seldom reported .…”
Section: Introductionmentioning
confidence: 99%
“…1,[3][4][5] In recent years, due to the advancement of imaging techniques such as transvaginal ultrasound scan (TVUS) and magnetic resonance imaging (MRI), substantial evidences suggest that adenomyosis may develop more often among younger women. 6,7 To date, no novel compound is reported to develop for adenomyosis and clinical studies on the well-conducted pharmacologic treatment are seldom reported. 8 The most effective treeatments of adenomyosis are invasive surgeries such as hysterectomy, which is unacceptable for the patients who want to preserve their fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Hormonal IUD are used as a contraceptive method [21] or in the therapy of several conditions such as: heavy bleeding [22], women at risk for thrombocytopenia [23], endometrial hyperplasia [24], abnormal uterine bleeding in premenopause [25], endometriosis [26], and adenomyosis [27]. Before inserting an IUD, the patient should be investigated thoroughly because the symptoms caused by the IUD insertion may delay the diagnosis of serious illnesses.…”
Section: Thinning Of Ujz Thickness After Treatment With Mirenamentioning
confidence: 99%
“…диагностика основана на клинической картине и данных, полученных с помощью неинвазивных методов обследования [10]. К клиническим проявлениям аденомиоза относят различные варианты аномальных маточных кровотече-ний, болевой синдром, диспареунию, приводящие к достоверному снижению качества жизни [11][12][13][14][15]. Последние исследования показали, что аденомиозу подвержены и молодые женщины, у которых заболевание ассоциировано с бесплодием и невынашиванием беременности [13,16,17].…”
unclassified
“…в настоящее время многие исследователи сходятся во мнении о необходимости создания единой систематической классификации аденомиоза, в том числе с помощью различных методов визуализации [12][13][14]. Поиск новых патогенетических механизмов развития заболевания с целью прогнозирования темпов, характера и выраженности клинических проявлений представляет научный и практический интерес.…”
unclassified